2004
DOI: 10.1007/s00586-003-0661-5
|View full text |Cite
|
Sign up to set email alerts
|

One-stage anterior interbody autografting and instrumentation in primary surgical management of thoracolumbar spinal tuberculosis

Abstract: There are few articles in the literature concerning anterior instrumentation in the surgical management of spinal tuberculosis in the exudative stage. So we report here 23 cases of active thoracolumbar spinal tuberculosis treated by one-stage anterior interbody autografting and instrumentation to verify the importance of early reconstruction of spinal stability and to evaluate the results of one-stage interbody autografting and anterior instrumentation in the surgical management of the exudative stage of thror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 14 publications
3
92
1
1
Order By: Relevance
“…Earlier apprehensions regarding the use of metal implants in the presence of active tubercular infection were overcome following the realization that tubercle bacilli had slow rates of division, lower bacillary counts than pyogenic infections, and do not produce adhesion molecule and bio-film [24,25]. Two reports of isolated anterior instrumented fusion have been published where the authors have claimed good results [26,27]. However, other authors have reported good outcomes with posterior fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier apprehensions regarding the use of metal implants in the presence of active tubercular infection were overcome following the realization that tubercle bacilli had slow rates of division, lower bacillary counts than pyogenic infections, and do not produce adhesion molecule and bio-film [24,25]. Two reports of isolated anterior instrumented fusion have been published where the authors have claimed good results [26,27]. However, other authors have reported good outcomes with posterior fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have considered anterior approach to be too invasive and often unnecessary in the context of spinal tuberculosis. Anterior approach may involve division of the diaphragm and segmental spinal vessels [26,27]. Campbell et al [30] have reported higher rates of complications with isolated anterior fusion and combined anterior and posterior spinal fusion compared to isolated posterior fusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of surgeons favour the anterior approach because of concern over the safety of the posterior approach [8,9]. The anterior surgical approach includes an anterolateral extrapleural approach and a transpleural anterior approach, which was developed by Hodgson et al [1,14] and has been used by many surgeons for spinal tuberculous lesions [2,[15][16][17]. The anterior approach is considered to be very important because it can provide the surgeon with direct access to the diseased vertebral segments to perform radical surgical debridement of the infected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In their study on stainless steel, Oga et al [24] reported that M. tuberculosis has low adhesion capability and forms only a few microcolonies surrounded by a biofilm. Benli et al, Yılmaz et al and Jin et al [1,14,33] showed that anterior implant can be safely used in tuberculous spondylitis. Liljenqvist et al and Hee et al [10,18] reported the titanium mesh cage to be safe in vertebral osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%